Effects of Ibuprofen intake in muscle damage, body temperature and muscle power in Paralympic powerlifting athletes - Fraga, G. S.; Aidar, F. J.; Matos, D. G.; Marçal, A. C.; Santos, J. L.; Souza, R. F.; Carneiro, A. L.; Vasconcelos, A. B.; Da Silva-Grigoletto, M. E.; van den Tillaar, R.; Cabral, B. T.; Reis, V. M. (International Journal of Environmental Research and Public Health, 2020)
The aim of this study is to evaluate the effect of ingesting ibuprofen on post-workout recovery of muscle damage, body temperature and muscle power indicators in Paralympic powerlifting athletes. The study was carried out with eight Paralympic powerlifting athletes (aged 27.0 ± 5.3 years and 79.9 ± 25.5 kg of body mass) competing at the national level, with a minimum training experience of 12 months, who all submitted to two experimental conditions: Ibuprofen (2 × 00 mg) and control. The maximal isometric force of the upper limbs and rate of force development, thermography, and serum biochemical analyzes of creatine kinase, lactate dehydrogenase, aspartate aminotransferase and alanine aminotransferase were measured before, after, 24 h after and 48 h after the intervention. Maximal isometric force only decreased in the placebo condition, which increased back to baseline levels, while no substantial decline in baseline force was seen in the ibuprofen condition, although no effect for exercise condition was detected. After the exercise, the rate of force development decreased significantly for both conditions and did not exceed baseline levels again after 48 h. Muscle temperature decreased significantly at 48-h post-exercise in the placebo condition, when compared with the previous day of measurement; and deltoid muscle temperature at 48-h post-exercise was higher with the ibuprofen condition. Although the results indicate some positive effects of ibuprofen use, they do not enable a clear statement regarding its positive effects on muscle function and muscle damage. Ibuprofen seems to have caused a delay in the anti-inflammatory response following exercise.